Study on shared key management scheme for WSN based on LEACH protocol - Min FAN; Jue JIANG; Lin TANG,Mo-ran QIU,Chao LI (网络与信息安全学报, 2016)
In order to achieve transmission safety,nodes longer life and higher operation efficiency for the hierar-chical wireless sensor network,a shared secret key management scheme for WSN based on LEACH protocol was proposed.The scheme has good integrity and timeliness,dynamic key safety,node security independence and key survival,and also has the ability to resist the man-in-the-middle attack,DDoS attacks and so on.Furthermore,en-ergy consumption is lower to distribute shared key,and efficiency is higher to operate network.